Pregnancy with Early Latent Syphilis, a reality in 21st century: a case report and literature review - Eighty Mardiyan Kurniawati; Rizqy Rahmatyah; Velyana Lie; Achmad Rheza (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Syphilis is a sexually transmitted disease caused by the spirochete Treponema pallidum. It is of special concern during pregnancy because can lead to adverse pregnancy outcomes and congenital syphilis. We retrospectively included female patient with laboratory-confirmed syphilis in East Java. Demographic, pregnancy record, clinical, radiological, laboratory, and treatment data were reviewed from medical record and health of both mother and child book. Clinical characteristics and outcome of patient were described. The patient was 40-year-old multiparous pregnant women was referred to the hospital at 40 weeks of gestation due to early latent syphilis. The patient was diagnosed during the last trimester and had not been treated, but no vulvar and anal genital wart was found. Patient was scheduled to urgent section caesarean but 1 hour after admitted to the hospital, patient had spontaneous delivery. A healthy son was born (3400 g /50 cm, 10 points Apgar score). Due to the lack of documentation regarding treatment of maternal syphilis, crystalline penicillin was administered to the newborn. Screening and early penicillin treatment are the most important factors that can eliminate complications related to the prenatal contagion with Treponema pallidum. Yet despite the lack of treatment or its inappropriate administration, the pregnancy complicated with maternal syphilis may end in a completely different way.